(untitled) (Indian Journal of Animal Production and Management, 2024)
Present study was conducted on twenty-three Surti buffaloes maintained at Livestock Research Station under Navsari Agricultural University, Navsari, Gujarat with the objective to study the general temperament and its effect on milking behaviour traits and milk yield. Important milking behavioural traits like total milking time, milk flow rate and milk yield per milking were recorded at the time of each milking. All of these parameters were recorded on day 6 postpartum thereafter at fortnight interval till 90th postpartum. The collected data were compiled, tabulated and analyzed by using SAS 9.2. Perusal of data revealed that during early lactation temperament of primiparous buffaloes found to be restless-nervous type. The temperament score was significantly higher (p<0.05) for primiparous than multiparous animals on day 6 (3.38±0.18 vs 1.87±0.19), 20 (2.50±0.19 vs 1.60±0.16) and 34 (2.13±0.29 vs 1.47±0.16) postpartum. Milking behavior traits like liking time and milk flow rate found to be higher for animals having docile-slight restless temperament and animals having docile-slight restless temperament produced significantly higher (p<0.05) milk yield in 100 days (492.13±42.81 vs 328.57±28.79 kg) than animals with restless and nervous temperament.